1983
DOI: 10.1136/adc.58.7.523
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of the aerobic and anaerobic faecal flora in neonatal necrotising enterocolitis.

Abstract: SUMMARY Faeces from 24 neonates with proved necrotising enterocolitis (NEC), from 12 with clinically suspected NEC, and from 41 control infants were quantitatively cultured under aerobic and anaerobic conditions. An important difference in colonisation with Klebsiella was found between the NEC groups and the control group. Although the cause of NEC is unknown, colonisation with Klebsiella seems to increase the risk.Necrotising enterocolitis (NEC) is found especially among preterm infants. Its principal clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…Moreover, several authors did not find any relation between the isolation of C. difficile and/or detection of its toxins and NEC (21,24,25). In Westra-Meijer's study (19), C. difficile colonization was similar in the NEC groups and the healthy group (~50%). However, in very rare cases, C. difficile might be involved in severe enterocolitis in infants, the most obvious relationship being in regards to enterocolitis in Hirschsprung's disease (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, several authors did not find any relation between the isolation of C. difficile and/or detection of its toxins and NEC (21,24,25). In Westra-Meijer's study (19), C. difficile colonization was similar in the NEC groups and the healthy group (~50%). However, in very rare cases, C. difficile might be involved in severe enterocolitis in infants, the most obvious relationship being in regards to enterocolitis in Hirschsprung's disease (26).…”
Section: Discussionmentioning
confidence: 99%
“…Westra-Meijer et al (19), comparing aerobic and anaerobic fecal flora in healthy preterm infants and infants with NEC, observed a higher colonization with Klebsiella species in infants with NEC but no difference in clostridia populations. Nevertheless, a careful analysis of the published results showed that the proportion of infants who were colonized with high levels of clostridia (Ն10 8 /g of feces) was higher in the two NEC groups (54%) than in the healthy group (25%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have explored the establishment of bacterial flora in term and preterm infants (2)(3)(4). Several studies noted that initial bacterial colonization could play a pivotal role in the development of NEC (5-7).…”
mentioning
confidence: 99%
“…from peritoneal fluid or blood and more severe disease. Clostridium bulyricum and Clostridium difficile have also been implicated in the pathogenesis of NEC [47,48] but these organisms are frequently iso lated from the stools of asymptomatic neo nates [49][50][51][52][53].…”
Section: Is Nec An Infection?mentioning
confidence: 99%